Evaluation of gingival crevicular fluid transforming growth factor-1 level after treatment of intrabony periodontal defects with enamel matrix derivatives and autogenous bone graft: A randomized controlled clinical trial - YARAT, AYŞEN; KURU, LEYLA; AĞRALI, ÖMER BİRKAN (MEDKNOW PUBLICATIONS & MEDIA PVT LTD, 2016)
Aim: The present study aimed to evaluate the effects of enamel matrix derivatives (EMD) either alone or combined with autogenous bone graft (ABG) applied to intrabony defects in chronic periodontitis patients on clinical/radiographic parameters and gingival crevicular fluid (GCF) transforming growth factor-1 (TGF-1) level and to compare with open flap debridement (OFD). Materials and Methods: A total of 30 deep intrabony defects in 12 patients were randomly treated with EMD + ABG (combination group), EMD alone (EMD group), or OFD (control group). Clinical parameters, including plaque index, gingival index, bleeding on probing, probing depth, relative attachment level, and recession were recorded at baseline and 6 months postsurgery. Intrabony defect fill percentage was calculated on the standardized radiographs. TGF-1 level was evaluated in GCF just before surgery and 7, 14, 30, 90, 180 days after surgery using enzyme-linked immunosorbent assay. Results: All treatment procedures led to significant improvements at 6 months (P 0.01). Gain in attachment level (P 0.01) and radiographic defect fill (P 0.05) of the combination and EMD groups were found to be significantly higher than those of the control group, while the use of EMD either with ABG or alone was observed to produce significantly less recession than the OFD (P 0.05). Conclusion: The findings suggest no clinical and radiographic differences between the combination and EMD groups whereas GCF TGF-1 level demonstrates an increase during the healing phase and is positively affected from EMD.
Keywords: Autogenous bone graft; chronic periodontitis; enamel matrix derivatives gingival crevicular fluid; periodontal bone loss; periodontal flap surgery; transforming growth factor; GUIDED TISSUE REGENERATION; BOVINE-DERIVED XENOGRAFT; OSSEOUS DEFECTS; TGF-BETA; INTRAOSSEOUS DEFECTS; BIOACTIVE GLASS; INFRABONY DEFECTS; GENE-EXPRESSION; PROTEINS; HUMANS